Second primary cancers after kidney cancers, and kidney cancers as second primary cancers - Zheng, Guoqiao; Sundquist, Kristina; Sundquist, Jan; Chen, Tianhui; Försti, Asta; Hemminki, Otto; Hemminki, Kari (European urology open science, 2021)
Background - Second primary cancers (SPCs) are increasing due to improving survival in first primary cancers. Previous studies on SPCs in renal cell carcinoma (RCC) have focused on treatment and other risk factors, but data of RCC as an SPC are scarce. - Objective - In this study, we want to elucidate the risk for any SPC after RCC, and in reverse order, for RCC as an SPC after any cancer. We additionally consider how family histories influence the risks. - Design, setting, and participants - Patient data were obtained from the Swedish Cancer Registry from years 1990 through 2015, and family data were obtained from the Multigeneration Register. - Outcome measurements and statistical analysis - We employed standardized incidence ratios to estimate bidirectional relative risks of subsequent cancer associated with RCC. - Results and limitations - We identified 17 587 RCCs (60% in male patients). The highest increases for SPCs were observed for nervous system hemangioblastoma (HB; 26.8), adrenal (12.09) tumors, and renal pelvic cancer (6.32). In the reverse order, RCC as an SPC, nervous system HB (17.01), and adrenal tumors (15.34) were associated with the highest risks. Risks for many other sites (12 sites and subsites) were increased bidirectionally. For women, a total of seven sites and subsites were increased bidirectionally, and many were shared with men. The only significant sex difference in SPCs was the higher lung cancer risk in women (2.41) than in men (1.28). Patients with a family history of HBs or of prostate, colorectal and lung cancers showed high risks of these cancers as SPCs after RCC. Family history accounted for 30% of prostate cancers after RCC. - Conclusions - The bidirectional study design was able to suggest risk factors for SPCs and offered a clinical take-home message urging to consider strategies for early detection and prevention of SPCs. Readily available information on lifestyle (eg, smoking) and family history (eg, prostate cancer) may reveal targets for risk reduction with prognostic benefits. - Patient summary - Close to 10% of kidney cancer patients develop another cancer. The cause for these other cancers may not depend on kidney cancer.
Gesehen am 17.03.2021